Administration of recombinant erythropoietin alone does not improve the phenotype in iron refractory iron deficiency anemia patients - Lehmberg, Kai; Grosse, Regine; Muckenthaler, Martina; Altamura, Sandro; Nielsen, Peter; Schmid, Hansjörg; Graubner, Ulrike; Oyen, Florian; Zeller, Wolfgang; Schneppenheim, Reinhard; Janka, Gritta E. (Annals of hematology, 2013)
Mutations in transmembrane protease, serine 6 (TMPRSS6) cause iron refractory iron deficiency anemia (IRIDA). Parenteral iron administration may slightly improve hemoglobin level but is troublesome for patients. Optimal treatment has yet to be determined. We identified five patients from four independent families displaying the IRIDA picture with truncating biallelic mutations in TMPRSS6, one of which is novel. Liver iron determined by superconducting quantum interference device biosusceptometry ranged from 390 to 720 µg Fe/g wet weight (normal range 100-500; n = 3). Intestinal iron absorption (12 and 32 %, normal range 10-50; n = 2) and 59Fe erythrocyte incorporation after ingestion of 59Fe (57 and 38 %, normal range 70-90; n = 2) were inadequately low for iron-deficient anemic individuals. Baseline serum erythropoietin was elevated or borderline high in four patients. Administration of recombinant human erythropoietin (rhEPO) at up to 273 and 188 U/kg body weight/week alone did not improve anemia or result in a decrease of urinary hepcidin in two individuals. In conclusion, the ability of exogenous rhEPO to increase hemoglobin level appears to be impaired in IRIDA.
Published online: 20 November 2012
Gesehen am 08.12.2021